Prediksi Minat Mahasiswa untuk Berwirausaha menggunakan Pendekatan Theory Of Planned Behavior - Ratna Listiana Dewanti; Taufik Bin Abad (Telaah Bisnis, 2016)
AbstractThis research aims to identify factors that influence the students’ motivation to run business based on theory of planned behavior. This research is conducted by examining the influence of students’ attitude againts its behavior, subjective norms and behavioral control on their intention to run business. The research samples are students of private university majoring in management because they have subject on Entrepreneur in the curriculum and for the reason of convenience. Research data are collected by distributing questionnaire to the students. Regression analysis is applied to analize 167 questionnaires sent back by the respondents. The result shows that the students’ attitude againts the behavior does not influence the intention to run business. While students’ attitude againts subjective norms and behavioral control do influence the intention to run business.